Analysis and modelling of influence factors in the configuration of a sustainable university: Case study: "Stefan cel Mare" University of Suceava - Daniela Mihaela Neamþu; Ruxandra Bejinaru; Cristian Valentin Hapenciuc; Iulian Condratov; Pavel Stanciu (Amfiteatru Economic Journal, 2020)
Universities create study programs and organize extracurricular activities to prepare future generations of professionals, political and social leaders for responsible actions towards sustainable development. The purpose of this research is to identify the determinant factors and their level of influence, regarding the framing of the strategies of Ştefan cel Mare University of Suceava in the pattern of the sustainable university. Through this research we explored, from the perspective of the bachelor and the master students as main stakeholders, how Ştefan cel Mare University of Suceava develops and sustains educational and extracurricular programs, in order to train the skills necessary for a sustainable development. We undertook an exploratory research, the results of which we processed through factorial analysis and logistic regression, carried out using SPSS v.20. The conclusions suggest that the analyzed university applies strategies in the direction of developing entrepreneurial skills, first of for the students and masters, so that in the long term it will ensure a sustainable development in the direction of social and environmental challenges. The research findings have practical implications for universities and can support the advancement of educational programs related to sustainable development so that students become change agents.
Keywords: I25; J24; L26; Q01; 330; sustainable university; influence factors; sustainable development; entrepreneurial skills; change agents